Epiglottic cyst as an etiological factor of globus sensation - Polat, Bahtiyar; Karahatay, Serdar; Gerek, Mustafa (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Globus is a subjective complaint that describes a sensation of a lump or a foreign body in the throat. Despite being a well-known and common clinical condition, the etiological factors have not been definitely elucidated yet. The study was set up to ascertain the relationship between epiglottic cysts and globus sensation. Materials and Methods: All patients undergoing investigation and treatments for globus sensation were included in the study. Patients with epiglottic cysts but no other possible causes of globus sensation were constituted the series of patients. Patients were asked to assess the levels of complaint before and after the carbon dioxide (CO2) laser excisions of the cysts. Results: Epiglottic cysts were found in 10 (5.4%) of the 182 patients. Three of these 10 patients who had concomitant diseases or conditions that may cause globus sensation and one patient who refused the surgery were excluded from the study. All the remaining six patients reported relief of the globus sensation after the CO2 laser excisions of the cysts. Conclusion: Our results, obtained from this limited series, indicated that epiglottic cysts may be considered as one of the etiological factors of globus sensation.